Molecular-scale hybrid membranes prepared with benzimidazole based monomers for high performance H2 purification - Luan, Liping; Shi, Puxin; Guo, Zhecheng; Cong, Shenzhen; Tang, Shenyi; Zhang, Bo; Wang, Zhi; Liu, Xinlei (Journal of membrane science, 2025)
For high performance H2 purification, molecular-scale hybrid membranes with benzimidazole rings and amide linkages were designed by one-step interfacial polymerization. The key is the employment of benzimidazole based monomers. The membrane structures were sufficiently characterized and separation capability of the membranes were feasibly regulated by preparation parameters and feed conditions. The optimized membrane displayed a stable permeance for H2 (around 500 GPU) with a H2/CO2 selectivity around 50 at 523 K and 2 bar, surpassing the upper bound of polymer membranes. [Display omitted] •Benzimidazole based monomers and Zr-oxo clusters are employed to prepare molecular-scale hybrid membranes.•The membranes fabricated by one-step interfacial polymerization contain benzimidazole rings and amide linkages.•The performance surpasses the upper bounds of polymer membranes for H2/CO2 separation.